The Meaning of Integrity among Public Officers: a Phenomenology Study - Idha Rahayuningsih; Suryanto Suryanto; Fendy Suhariadi; Cholichul Hadi (Journal of Educational, Health and Community Psychology, 2022)
Good governance can be realized if public officials have integrity. The integrity of public officials is a source of public trust in the government's performance in providing public services. This research aims to describe the meaning of integrity and internal factors that strengthen integrity from the perspective of public officials. Our study used a qualitative method based on phenomenological philosophy. Participants were selected based on three criteria: (1) echelon II officials as Heads of Regional Government Work Units, (2) have excellent work performance, and (3) have never violated the code of ethics, regulations, and laws. We conducted face-to-face, in-depth interviews to collect the data and analyze the data using. Our findings reveal eight meanings of integrity by public officials and internal factors that strengthen integrity. Eight meanings of integrity include carrying out duties and obligations seriously; being honest in carrying out tasks; discipline, complying with procedures and regulations; consistency between values/principles and behavior; being fair; having moral courage; being a role model for subordinates; not abusing position for personal gain or specific parties. Meanwhile, internal factors that strengthen integrity include: social-oriented terminal value, moral-oriented instrument value; competency-oriented instrument value, self-awareness as a public servant, simple lifestyle, change motivation, learning motivation, and achievement motivation.